Vietnam - Nickelson, Harry (San Diego, CA : Lucent Books, 1989)
An account of the Vietnamese Conflict and its aftermath, with information on its origins and on how the war affected American foreign policy and attitudes even today.
Includes bibliographical references (p. 92) and index.
Keywords: Vietnamese Conflict, 1961-1975 -- Juvenile literature; Vietnamese Conflict, 1961-1975 -- United States -- Juvenile literature; United States -- History -- 1945- -- Juvenile literature